Rhetorical Moves in Problem Statement Sections of Postgraduate Theses of English Education Study Program - Rizki Denarti; Hilda Puspita; Mukhrizal Mukhrizal (Universitas Bengkulu, 2021)
This research is aimed to find out kind of moves, the dominant moves and steps and the most common pattern of rhetorical moves in Postgraduate Theses of English Education Study Program Students at the University of Bengkulu in the academic year 2018 and 2019. The documentation technique and checklist were used in this research. Twenty six theses were analyzed by using checklist analysis from Swales’ CARS Model (1990). The results showed that Move 1 (Establishing a Territory), Move 2 (Establishing a Niche) and Move 3 (Occupying the Niche) were found in each thesis. The writers dominantly use Move 2 and Step 1B (Indicating a Gap) and the other step is Step 1A (Outlining Purposes) of Move 3. That is to say, the writers understood that Move 2 was the key component of Problem Statement (PS), and that makes Move 2 as the obligatory move. Further, the most common pattern is Incomplete Pattern. The PS which has this pattern only involved one move in it. Meanwhile, the other PS which has two moves which belong to Semi-Complete and another one has three moves, and it belongs to Complete Pattern. In conclusion, the Problem Statement by Postgraduate Students of English Education Study Program did not follow the required structure of CARS Model by Swales (1990).